2017
DOI: 10.1177/1742271x17721264
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of thoracic ultrasonography in diagnosis and staging of bronchogenic carcinoma

Abstract: Thoracic-ultrasound has a significant complementary role to computed tomography in diagnosis and staging of bronchogenic carcinoma. Thoracic-ultrasound-guided biopsy revealed good positive yield (78%), its yield was negatively affected by mass size and necrosis. It is a simple, practical and accurate procedure without significant patients' risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…2 Another smaller study of 54 patients reported there was no significant difference in identifying chest wall invasion with ultrasound detecting changes in 20.8% patients whereas CT detected this in 11.3% patients. 8 Ultrasound in this case could not identify the mediastinal lymphadenopathy, and the full staging and assessment of lung cancers should be made with CT. When scanning soft tissue masses, it is important to not only assess the soft tissues but also assess bony structures.…”
Section: Discussionmentioning
confidence: 79%
“…2 Another smaller study of 54 patients reported there was no significant difference in identifying chest wall invasion with ultrasound detecting changes in 20.8% patients whereas CT detected this in 11.3% patients. 8 Ultrasound in this case could not identify the mediastinal lymphadenopathy, and the full staging and assessment of lung cancers should be made with CT. When scanning soft tissue masses, it is important to not only assess the soft tissues but also assess bony structures.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, a necrotic tumor/cystic part of a tumor can be avoided and chances of rebiopsy can be minimized. 9 Newer advances in ultrasound like CEUS can help in better microvascular assessment and help in differentiating tumor showing heterogeneous enhancement with early washout from atelectasis which shows uniform marked and sustained enhancement. Infarct appears as non-enhancing tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This can help the radiologist with a better idea of what should be the best site to biopsy. Thus, a necrotic tumor/cystic part of a tumor can be avoided and chances of re‐biopsy can be minimized 9 …”
Section: Discussionmentioning
confidence: 99%
“…Over the last 10 years, several papers have confirmed the usefulness of LUS in specific settings . In particular, the accuracy of LUS is at least not inferior to CXR in the diagnosis and monitoring of pneumothorax (PTX), pleural effusion, interstitial syndrome (IS) and community‐acquired pneumonia (CAP) .…”
Section: Introductionmentioning
confidence: 99%